2011
DOI: 10.1007/s00590-011-0845-3
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid reduces blood loss in simultaneous bilateral total knee arthroplasty: a randomized control trial

Abstract: Total knee arthroplasty (TKA) is a common procedure, and bilateral TKA ensures cost efficiency. Bilateral TKA is associated with increased requirement of blood transfusion (BT). BT is associated with hazards, therefore be avoided. Tranexamic acid (TXA) has been suggested to reduce the BT, and the use of TXA in bilateral TKA appears sparse in literature. This study aimed at assessing the effect of TXA in such patients. This prospective randomized controlled trial evaluated the use of TXA in bilateral TKA. Pre-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…Of the included studies, 12 articles were in English [920] and 3 were in Chinese, [21–23] and all were published in 2009 or later. The characteristics of the studies that were included are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the included studies, 12 articles were in English [920] and 3 were in Chinese, [21–23] and all were published in 2009 or later. The characteristics of the studies that were included are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…All the included studies were published in 2009 or later, and most of the studies were from the year 2014. Four RCTs [12,14,19,20] were of high quality and 3 RCTs [15,16,22] did not state the random sequence generation. Two studies [16,22] did not involve allocation concealment, blinding of participants and personnel and blinding of the outcomes, and 1 RCT [21] is unclear concerning these criteria.…”
Section: Discussionmentioning
confidence: 99%
“…23 The TXA group had a smaller decrease in haemoglobin level (1.29 vs. 1.46 g/dl), less blood loss in the drain (402 vs. 569 ml), and required fewer allogeneic blood transfusion units (0.07 vs. 0.3 units) than those without TXA. 12 Intravenous TXA, intra-articular TXA injection after wound closure, and an intra-articular TXA wash after cementing of implants and before closure of the retinaculum are comparably effective. 14,15,24,25 The intra-articular TXA wash can directly target the site of bleeding within a contained joint cavity; it reduces the marked increase in local fibrinolysis after release of the tourniquet, and increases microvascular haemostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Neither intravenous nor intra-articular TXA result in an increased risk of thromboembolic complications. [7][8][9][10][11][12][13]23 The haemoglobin balance method takes into consideration the amount of hidden blood loss that cannot be directly measured by the drain output. 26 Intra-operative blood loss can also be estimated by: (1) subtracting the total amount of wash given from the total suction volume intra-operatively, or (2) subtracting the weight of used swabs from their original weight (1 g=1 ml).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation